Health Policy Development During COVID-19 in Saudi Arabia: Mixed Methods Analysis - Alonazi, Wadi B.; Altuwaijri, Eman A. (Frontiers in Public Health, 2022)
Healthcare systems are increasingly required to utilize effective approaches, apply evidence based practice, and consequently sustain successful strategic management. Document analysis provides insights into the effectiveness management tools applied by agencies to respond to crises. This paper provides a practical exploration of how the Saudi health authority applied effective measures to eventually reduce the administrative and clinical consequences while managing the COVID-19 pandemic. The conceptual descriptive framework was based on Walt and Gilson’s health policy triangle (HPT). Official reports and supporting documents issued by the Saudi government towards COVID-19 were operationally analyzed. Moreover, five healthcare professional experts were invited in a semi-structured interview to assess the strategic steps that have been utilized to minimize the health risk by conducting healthcare risk analysis. Various documents showed that two major entities were responsible for managing regulations and medications of COVID-19 in addition to six other entities that were partially involved. Although each entity approved to work independently, their efforts were cohesively associated with each other. Most documents were well-applied on personal, social, organizational, and national strata. However, it is unclear how lessons identified became affirmative, while the collaboration remains vague, especially under the emergence of the new entity like the Public Health Authority. Healthcare professional experts also positively supported the effectiveness of such policies to confront COVID-19 through three domains: health guidelines; utilizing simulation (telehealth/telecommunication) services; and ensuring continuity of services.